Intoxicações ocupacionais por inseticidas organofosforados: análise epidemiológica de casos registrados em Fortaleza e avaliação da ocorrência em agentes sanitários que trabalham no combate ao dengue - Ribeiro, José Luciano Xavier (2000)
The crescent use of organophosphate insecticides has been a source of danger for the health of some workers( mainly the Health Agents) and community who frequently handle those products in the combat of diseases. This study investigates the ocorrence of occupational intoxications by organophosphate insecticides in Fortaleza, by an epidemiologic analysis of reported cases in Toxicollogy Attending Center - CEATOX, of 1995 to 1998, and by an evaluation of the health, risks and work conditions of the Health Agents of the Health National Foundation-FNS that use every day these insecticides . The data, intoxications general. It was also observed 319 cases (2,2%) out of total were reported as occupational intoxications with a fali of 33% in the final period. From those cases, 58(18,2%) were caused by pesticides and from these(n=28cases), 48,3% were organophosphate insecticides. During the study of the sample, 3 variables were analysed (sex, age, origin), sex which presented a prevalence of intoxication in males (75%), in the age range of 15 to 60 years old (64,3%), living in urban zone (85,7%). A transverse study for the evaluation of the health, risk and work conditions of 52 Health Agents of FNS was performed in the UBV(Cleanning) Support Station of Health National Foundation (FNS), situated at the City of Euzébio, 30Km from Fortaleza-Ce. A questionaire with 28 items was used as instrument to collect data and 8 variables were analysed: age range, time of insecticide manipulation, individual protection, use of the back applicator (machine cleaning), social habits, common diseases and health status. It was observed that the work conditions of the Health Agents are satisfactory and suitable to dengue control with few risks to the worker health. The majority of Agents(55,8%) the is in the age range of 30 to 40 years old. Also, it was observed that most Agents has a good health status without vices (54% abstemíous), diseases (69%) and intoxications (92%). !t was concluded that this situation was achieved by the care, fiscalization, training and biological monitoring executed by FNS. Finally, it was concluded that the actuai profile of occupational intoxication by organophosphate insecticides in Fortaleza, during lastyears, can not be defined in a concíusive way with the data acquired in this work. The reasons are the non suitability of the data source (CEATOX-IJF) due to its nature of emergency hospital and the small size of the sample which may not reflect the actual picture of the problem.